Configurations of collective mental models in solving service and combat tasks by cadets of the National Guard - Нуржан С. Мекебаев; Юлия М. Перевозкина; Михаил В. Федоришин (Rossijskij psihologičeskij žurnal., 2022)
Introduction. A collective mental model as an important component of a military team, whose members have different knowledge, experience, needs, values, can effectively explain, predict and improve the success of a military unit in the performance of combat missions. The novelty of this work lies in the use of a metasystem approach to develop the structure and methods for measuring the collective mental model of servicemen when they solve non-standard situations in peacetime and wartime. The purpose of the study was to develop a structure and method for measuring the collective mental models of military personnel. The assumption was tested that when solving various introductory cadets, different knowledge, abilities, emotions, needs and roles will be used. Methods. The study involved 71 cadets of the VOOVO of the troops of the National Guard of the Russian Federation aged 21 to 27 years. To study individual mental models, 10 cases were developed containing real everyday and service-combat situations. When solving each introductory cadet, it was necessary to determine the cognitive, motivational, emotional and role parameters. To identify role aspects, the Kaleidoscope technique was used, containing 10 figures divided by gender and age. To identify collective mental models for each input, an analysis of the contingency of the parameters under study was used according to the Pearson criterion. R results. When solving the introductory cadets, statistically significant associations were found regarding the presence of existing similar experience, metcognitive knowledge, abilities, needs, emotions and roles (p≤0.05). About the discussion of the results. The results of the study confirmed the assumption that the obtained connections make it possible to build certain configurations of collective mental models when military personnel solve problematic everyday and service-combat tasks. Conclusion. In general, the data of the conducted study allow us to conclude that the formation of a common mental model of military personnel can improve the understanding of service and combat missions by the personnel of the unit, promote mutual understanding and support in the military team, and also increase its effectiveness in military professional activities.